Local tourism accommodations and institutional strengthening in the interior of the Algarve, Portugal: the role of legislation and technology - Machado, Virgílio (2019)
Purpose: This study sought to understand how legislation and technology can enhance socio-economic development in low density population territories, focusing specifically on the dynamics of local tourist accommodation over the last decade. Design/methodology/approach: A case study was conducted for five municipalities in one of the most significant tourism regions of Portugal - the Algarve - based on a systematic investigation of relevant laws, regulations and electronic platforms. Official statistics were compiled and analyzed for the five territories’ registered local accommodation services, population, overnight stays, and additional local services. Findings: The results reveal that public entities’ regulations favor microentrepreneurship initiatives in local accommodation and that digital tools supported by online platforms have quite visible effects on low density territories. The findings also reveal that the local tourist accommodation supply has experienced an especially dynamic, sustained growth over the last decade. This expansion has been accompanied by an increased supply of other services, suggesting that accommodation can positively influence the existing and/or future socio-economic development of low density territories. Research limitations/implications: Further studies focusing on other areas with low density populations are needed to determine more clearly how local accommodation influences socio-economic development.